Challenges and Solutions in Teaching English for Students with Different Language Backgrounds (A Case Study in Torphan Rojjanawich School, Satun, Thailand) - Fabianto, Eko; Gadis Inayatul Aeni (English Education Journal, 2025)
This study investigates the challenges faced by teachers in teaching English to students from diverse language backgrounds at Torphanrojjanawich School, Satun, Thailand. It explores the linguistic, cognitive, and socio-cultural barriers impeding the acquisition of English, focusing on how these issues impact learning outcomes. Through qualitative data collected from interviews with teachers, classroom observations, and student surveys, the research identifies key obstacles such as the differences in native languages, limited exposure to English outside the classroom, and varying levels of cognitive readiness for language learning. Furthermore, the study presents strategies and solutions that have been implemented, including differentiated instruction, multimedia tools, and peer learning, and fostering bilingual/multilingual support systems. Findings suggest that while significant challenges exist, targeted interventions, teacher development, and institutional support can improve students' English proficiency in multilingual settings.